2x-5(x-13)=35

Simple and best practice solution for 2x-5(x-13)=35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-5(x-13)=35 equation:


Simplifying
2x + -5(x + -13) = 35

Reorder the terms:
2x + -5(-13 + x) = 35
2x + (-13 * -5 + x * -5) = 35
2x + (65 + -5x) = 35

Reorder the terms:
65 + 2x + -5x = 35

Combine like terms: 2x + -5x = -3x
65 + -3x = 35

Solving
65 + -3x = 35

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-65' to each side of the equation.
65 + -65 + -3x = 35 + -65

Combine like terms: 65 + -65 = 0
0 + -3x = 35 + -65
-3x = 35 + -65

Combine like terms: 35 + -65 = -30
-3x = -30

Divide each side by '-3'.
x = 10

Simplifying
x = 10

See similar equations:

| 2(2x-4)=392x-4 | | 12X+54000=15X | | 13X+48000=16X | | 2q=-10 | | -3-2+(-8)-5= | | 16x+20y=24 | | 5n-3=6n+8 | | 2x^2+36x+100=0 | | (2w-4)w=160 | | 10x^2-12x+36=0 | | 2(3n)=4n | | 8x+10y=30 | | 4a+2a=12 | | 2x^2+7x=-8 | | 5n-2+3m=5 | | -5-12= | | 16-12k= | | 2(x+3)-26=7(1-x) | | 2(x+3)-26=7(1-x) | | 2c-2=17 | | 2(x+3)-26=7(1-v) | | 2X+897.50=5277.50 | | r=2m+8 | | 0.33x=x-8 | | 8x^2+4y^2=-5 | | -250=50n | | x^2-12-36=0 | | x(x+3)=y | | 4n^2+10n=14 | | 8+(-24)+12= | | x^2-6x-13=0 | | 6x-10=-3+2x+3(5-2x) |

Equations solver categories